2019
DOI: 10.1108/hff-12-2018-0826
|View full text |Cite
|
Sign up to set email alerts
|

Fluid–structure interaction of free convection in a square cavity divided by a flexible membrane and subjected to sinusoidal temperature heating

Abstract: Purpose The purpose of the present paper is to model a cavity, which is equally divided vertically by a thin, flexible membrane. The membranes are inevitable components of many engineering devices such as distillation systems and fuel cells. In the present study, a cavity which is equally divided vertically by a thin, flexible membrane is model using the fluid–structure interaction (FSI) associated with a moving grid approach. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…References 77,78 have studied transient natural convection within a square cavity with flexible diagonal and vertical partitions, respectively. Reference 79 has solved a similar problem with sinusoidal wall heating. Trapezoidal cavities with deformable vertical partitions have been considered in Reference 80.…”
Section: Numerical Examplesmentioning
confidence: 99%
“…References 77,78 have studied transient natural convection within a square cavity with flexible diagonal and vertical partitions, respectively. Reference 79 has solved a similar problem with sinusoidal wall heating. Trapezoidal cavities with deformable vertical partitions have been considered in Reference 80.…”
Section: Numerical Examplesmentioning
confidence: 99%
“…Growing industry means increasing energy demand. On the other hand, world population growth has increased the number of energy consumers (Alsabery et al , 2019 and Ghalambaz et al , 2020).…”
Section: Introductionmentioning
confidence: 99%
“…According to the results, the tilting angle of the cavity has a significant impact on natural convection, and as a result, the concave or convex shape of the membrane is also influenced by the tilting angle of the cavity. Mehryan et al 11 explored numerically the natural convection within a regular quadrilateral enclosure that is regularly heated by a sinusoidal time variable temperature on the left vertical wall and chilled isothermally on the right vertical wall. The results revealed that the temperature frequency does not influence the mean values of the Nusselt number or the deformation of the flexible divider.…”
Section: Introductionmentioning
confidence: 99%